Human amniotic membrane as a chondrocyte carrier vehicle/substrate: in vitro study - Krishnamurithy, G.; Shilpa, P.N.; Ahmad, R.E.; Sulaiman, S.; Ng, C.L.L.; Kamarul, Tunku (2011)
Human amniotic membrane (HAM) is an established biomaterial used in many clinical applications. However, its use for tissue engineering purposes has not been fully realized. A study was therefore conducted to evaluate the feasibility of using HAM as a chondrocyte substrate/carrier. HAMs were obtained from fresh human placenta and were process to produced air dried HAM (AdHAM) and freeze dried HAM (FdHAM). Rabbit chondrocytes were isolated and expanded in vitro and seeded onto these preparations. Cell proliferation, GAG expression and GAG/cell expression were measured at days 3, 6, 9, 12, 15, 21, and 28. These were compared to chondrocytes seeded onto plastic surfaces. Histological analysis and scanning electron microscopy was performed to observe cell attachment. There was significantly higher cell proliferation rates observed between AdHAM (13-51, P=0.001) or FdHAM (18-48, p=0.001) to chondrocytes in monolayer. Similarly, GAG and GAG/cell expressed in AdHAM (33-82, p=0.001; 22-60, p=0.001) or FdHAM (41-81, p=0.001: 28-60, p=0.001) were significantly higher than monolayer cultures. However, no significant differences were observed in the proliferation rates (p=0.576), GAG expression (p=0.476) and GAG/cell expression (p=0.135) between AdHAM and FdHAM. The histology and scanning electron microscopy assessments demonstrates good chondrocyte attachments on both HAMs. In conclusion, both AdHAM and FdHAM provide superior chondrocyte proliferation, GAG expression, and attachment than monolayer cultures making it a potential substrate/carrier for cell based cartilage therapy and transplantation. (C) 2011 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 99A: 500-506, 2011.